Trends and predictors of glycosylated haemoglobin A1C, blood pressure, and LDL-Cholesterol among patients with type 2 diabetes in Negeri Sembilan, Malaysia / Wan Kim Sui - Wan, Kim Sui (2021)
Cardiovascular disease and diabetes pose enormous disease burdens globally and in Malaysia. Concurrent attainment of glycosylated haemoglobin A1C, blood pressure (BP), and LDL-cholesterol (LDL-C) goals, or collectively known as the “ABC” goals, help prevent cardiovascular complications in patients with type 2 diabetes (T2D). Numerous studies have reported suboptimal achievement of all three ABC goals, and clinical inertia in diabetes management is one primary reason for poor A1C control. However, such information is lacking in Malaysia. Hence, this study aims to: a) determine the proportion of T2D patients who achieved all three ABC goals at study baseline and exit and the associated factors in Negeri Sembilan, Malaysia; b) describe the A1C, systolic BP, diastolic BP, and LDL-C trends from 2013 to 2017 and determine the predictors of these trends; and c) determine the time to treatment intensification and the factors associated with treatment intensification in patients with uncontrolled A1C. A five-year retrospective open cohort study from 2013 to 2017 was conducted using data from the National Diabetes Registry, where six different datasets were merged to form a cohort dataset. Multivariate binary logistic regression was used to determine the factors associated with the attainment of all three ABC goals at the study baseline. Intervalcensored proportional hazards modelling was carried out to determine the factors associated with the achievement of all the ABC goals at cohort exit. Meanwhile, linear mixed-effects modelling was conducted to describe the A1C, systolic BP, diastolic BP, and LDL-C trends and determine the trends’ predictors. Life table survival analysis was carried out to determine the time to treatment intensification among patients with uncontrolled A1C. Proportional hazards modelling was used to determine the factors associated with treatment intensification. The attainment of all three ABC goals had improved from 4.5% to 5.8% (P <0.001) but remained suboptimal. Blood pressure was the limiting factor in achieving the triple targets as only 22.3% to 24.1% of patients iv achieved the BP goal. During the study period, the A1C and systolic BP trends had worsened (P <0.001 for both). The A1C excess of 1.07% in 2017 represented about 22% higher risk of diabetes-related death, myocardial infarction, and stroke, which were the biggest potentially avoidable CVD burdens among the three ABC parameters. Although the LDL-C trend improved consistently from 2.97 to 2.77 mmol/L, the mean values were still above the treatment goal of <2.6 mmol/L. Clinical inertia in T2D management was evident. The median time to treatment intensification was more than one year, and less than 50% of patients with uncontrolled A1C had treatment intensification. There were demographic differences whereby non-Chinese ethnic groups and younger adults had the most inadequate control of ABC. Higher body mass index categories and more intense treatment modalities were independent predictors for poorer ABC outcomes. Opportunities exist for further improvement as targeted interventions can be directed at the identified high-risk populations. More studies are needed to explore the underlying causes of clinical inertia in Malaysia so that effective strategies can be developed to address this issue. Keywords: blood pressure, cholesterol, clinical inertia, glycosylated haemoglobin A1C, type 2 diabetes